Tinjauan Sosiologis Terhadap Pembagian Hak Waris Tanah Menurut Hukum Waris Adat Toraja Pa’ Rinding di Lembang Batualu Kecamatan Sangalla’ Selatan - Marchelina Rante; Yulianus M. Rombeallo (UNES Law Review, 2023)
In the customary inheritance division in Lembang Batualu, South Sangalla' Subdistrict, it is known as Pa' Rinding, which is the distribution of inheritance based on the number of buffalo or pig sacrifices made by the heirs when the deceased passes away. In the Pa' Rinding inheritance division, the rights of other heirs can be forfeited, meaning that inheritance rights are transferred only to specific individuals. Despite the modern times, such rules are still applied and firmly upheld by some Toraja communities. Additionally, the rules and procedures in the Ma' Rinding process are not clearly defined within the inheritance laws of the Indonesian Civil Code (KUH Perdata). The research method employed in this study is empirical juridical, which examines the applicable legal provisions and their practical application in society. The research findings confirm that the procedure for the transfer of inheritance rights in Pa' Rinding is within the inheritance legal system used in Lembang Batualu, South Sangalla'. The transfer of inheritance rights occurs after the death of an individual who possessed assets and heirs. Furthermore, Pa' Rinding is intertwined with the rambu solo’ ceremony (funeral ceremony), where there are provisions for the heirs to make sacrifices of buffalo or pigs during the rambu solo' ceremony. These sacrifices serve as the basis for the subsequent heirs to manage the deceased's estate. The limitations on the assets that can be distributed to the heirs in the Pa' Rinding process in Lembang Batualu, South Sangalla', are based on the nature of the assets. Only the assets that were the livelihood of the deceased can be distributed through Pa' Rinding, while ancestral property or tongkonan land, which is communal property, cannot be divided further.